2008
DOI: 10.1021/jp8063382
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Dynamics of Excited 2-(3-Benzoylphenyl)propionic Acid (Ketoprofen) with Histidine

Abstract: Photoreaction dynamics of 2-(3-benzoylphenyl)propionic acid (ketoprofen, KP), one of nonsteroidal anti-inflammatory drugs, with histidine in a phosphate buffer solution (pH 7.4) was investigated with the laser flash photolysis. The deprotonated form of KP (KP(-)) was decarboxylated via UV laser excitation to form a carbanion. It was found that histidine accelerates the protonation reaction of the carbanion to 3-ethylbenzophenone ketyl biradical (3-EBPH) for the first time. The experimental results of the photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…In the phosphate buffer solution of pH 7.4, almost all KP exists in the deprotonated form of KP (KP − ) because of its acidity (p K a = 4.7). According to the previous report , an intense band around 600 nm appearing immediately after the laser irradiation was due to KP carbanion, and the band around 525 nm at 1.7 μs after the laser was assigned to EBPH. The same spectra were obtained with Tyr.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…In the phosphate buffer solution of pH 7.4, almost all KP exists in the deprotonated form of KP (KP − ) because of its acidity (p K a = 4.7). According to the previous report , an intense band around 600 nm appearing immediately after the laser irradiation was due to KP carbanion, and the band around 525 nm at 1.7 μs after the laser was assigned to EBPH. The same spectra were obtained with Tyr.…”
Section: Resultsmentioning
confidence: 83%
“… *Reference ; †For amino acids and dipeptides, correction of the concentration should be required because actual quencher for carbanion was the protonated form to the side chain of basic amino acids and dipeptides ; ‡Reference ; §Reference ; ∥Reference ; ¶This work. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous articles, we examined photoreaction of KP with triethylamine in methanol (18) and histidine (His) in phosphate buffer solution (Fig. 2; 19). It was found that the lifetime of carbanion became shorter and the yield of EBPH larger under the presence of His for the first time.…”
Section: Introductionmentioning
confidence: 99%